2008
DOI: 10.1123/jpah.5.s1.s126
|View full text |Cite
|
Sign up to set email alerts
|

BMI-Referenced Cut Points for Pedometer-Determined Steps per Day in Adults

Abstract: Background-The goal of this study was to establish preliminary criterion-referenced cut points for adult pedometer-determined physical activity (PA) related to weight status defined by body mass index (BMI).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
46
2
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(54 citation statements)
references
References 24 publications
5
46
2
1
Order By: Relevance
“…However, they were able to enter their data on the website at any time. Participants received personalized feedback on progress via: 1) weekly weight and step graphical MMS charts that depicted the previous 5 weeks; and 2) a daily pedometer goal for the upcoming week, calculated by averaging the daily steps from the previous week and adding 750 until they reached a daily average of 12,000 steps, recommended for weight loss (Tudor-Locke et al, 2008). After 12,000 steps were reached, the focus changed to encourage increased PA time or work at a faster pace, also relevant for weight loss.…”
Section: Interventionmentioning
confidence: 99%
“…However, they were able to enter their data on the website at any time. Participants received personalized feedback on progress via: 1) weekly weight and step graphical MMS charts that depicted the previous 5 weeks; and 2) a daily pedometer goal for the upcoming week, calculated by averaging the daily steps from the previous week and adding 750 until they reached a daily average of 12,000 steps, recommended for weight loss (Tudor-Locke et al, 2008). After 12,000 steps were reached, the focus changed to encourage increased PA time or work at a faster pace, also relevant for weight loss.…”
Section: Interventionmentioning
confidence: 99%
“…Each intervention participant’s long-term goal was to increase and maintain their step counts to 12,000 steps per day. 14 The intervention also included goals for achieving healthy reductions in total caloric and fat intake based on the DPP recommendations. In addition, intervention participants were advised to reduce consumption of sugar-sweetened beverages by replacing them with non-sweetened alternatives.…”
Section: Interventionmentioning
confidence: 99%
“…Wareham, et al [73] suggested that there is a requirement for a minimum of 45-60 minutes per day of moderate intensity physical activity to prevent the development of obesity but Slentz et al [74] have suggested that as little as 30 minutes of moderate physical activity per day would be sufficient for weight control. The consensus appears to be that an additional 3000 walking steps per day (equivalent to approximately 30 minutes of activity) over and above normal daily activity is necessary for a healthy lifestyle [75][76][77]. This goal could be achieved simply by increasing the activities of daily living rather than a formalised exercise prescription which might be difficult for individuals to adhere to.…”
Section: The Role Of Physical Activity In Reducing Obesity-related Cmentioning
confidence: 99%